ChemInform Abstract: Three‐Component Condensation for the Construction of Novel Spirooxindoles. Issue 22 (13th May 2013) - Ji, Fei; Sun, Mu; Lv, Mei‐fang; Yi, Wen‐bin; Cai, Chun
Abstract A convenient one‐pot procedure permits the synthesis of target compounds via reaction of isatylidene derivatives with zwitterionic species, generated in situ from alkynes and isocyanides.